A method for recycling waste wind power blade glass fiber plate

CN122999649APending Publication Date: 2026-10-30HENAN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611472401.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有回收技术中,破坏性方法导致纤维结构损伤、价值降低,非破坏性方法无法克服原板材各向异性的缺陷,以及本领域长期未能突破的从热固性层压板中连续、低损伤剥离柔性纤维薄片的技术瓶颈

Benefits of technology

[0014]本发明的有益效果为:实现了连续玻璃纤维的高形态保留与高值化回收。本发明采用分级楔入分层策略,通过精确控制分离路径沿层间弱界面推进,能够将废弃风电叶片厚板逐级解离为厚度可控的连续长条形层片,所得第一级玻纤层片无断裂、无分层缺陷,其拉伸强度、抗弯强度和层间剪切强度分别可达原始风电叶片玻纤板的95~99%、94~98%和92~98%,充分保留了原有玻璃纤维的长度和力学强度,显著提升了回收产物的经济价值与再利用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999649A_ABST
    Figure CN122999649A_ABST
Patent Text Reader

Abstract

The embodiment of the application discloses a kind of recycling methods of waste wind power blade glass fiber plate, method includes: waste wind power blade glass fiber plate is cut into columnar blank along fiber direction;Local heating is carried out to the wedge starting end of blank, only make the resin matrix in the region of wedge starting end soften to rubber state, and the remaining main part of blank maintains the rigid state of unheating;Using wedge-shaped blade, from the resin matrix of rubber state by wedge starting end, and by the rigid support of main part, make wedge-shaped blade continuously advance along interlayer interface, obtain first stage glass fiber sheet and heat it as a whole, make its internal resin matrix soften to rubber state by heating, send first stage glass fiber sheet after heating into roll cutting layering device and carry out layering stripping, obtain second stage glass fiber sheet.The method in the application realizes the high form retention and high value recycling of continuous glass fiber, significantly improves the economic value and reuse potential of recycled product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization technology, and more specifically, to a method for recycling waste wind turbine blade fiberglass boards. Background Technology

[0002] Waste wind turbine blades, including core structural components such as skin, spars, and webs, are typically manufactured using glass fiber reinforced epoxy resin (GFRP) laminates. After curing, the epoxy resin forms a highly cross-linked three-dimensional network structure, endowing the material with excellent mechanical properties and chemical stability, but also preventing it from being directly melted and reshaped like thermoplastic materials. With the approaching decommissioning of wind turbines, the green treatment and high-value utilization of large quantities of waste wind turbine blades has become an urgent problem to be solved. Existing recycling technologies suffer from destructive methods that damage the fiber structure and reduce its value, while non-destructive methods cannot overcome the anisotropy of the original substrate, and the long-standing technical bottleneck of continuously and minimally damagingly peeling flexible fiber sheets from thermosetting laminates remains unresolved. However, the high-value continuous glass fibers contained in the blades, if recovered and recombined into recycled boards with balanced mechanical properties in the form of structurally intact long strips, have a much higher reuse potential than pulverized fillers or simply cut profiles. However, achieving this goal faces significant technical challenges. Summary of the Invention

[0003] The purpose of this invention is to provide a method for recycling wind turbine blade fiberglass sheets by wedging a heated blade into layers, achieving high morphological preservation and high-value recycling of continuous glass fibers. This invention employs a staged wedging and layering strategy, precisely controlling the separation path along the weak interlayer interfaces to progressively dissociate the thick sheets of waste wind turbine blades into continuous, elongated strips of controllable thickness. The resulting first-stage fiberglass sheets are free of breakage and delamination defects, and their tensile strength, flexural strength, and interlayer shear strength reach 95-99%, 94-98%, and 92-98% of the original wind turbine blade fiberglass sheets, respectively. This fully preserves the original glass fiber length and mechanical strength, significantly enhancing the economic value and reuse potential of the recycled products.

[0004] This invention provides a method for recycling fiberglass boards from waste wind turbine blades, the method comprising: S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction; S2, the starting end of the blank is locally heated, so that only the resin matrix in the area of ​​the starting end of the blank is softened to a rubber state, while the main body of the blank other than the area of ​​the starting end of the blank is kept in an unheated rigid state. S3, a wedge-shaped blade is used to wedge into the fiber interlayer interface from the starting area of ​​the wedge, starting from the rubbery resin matrix, and the wedge-shaped blade is continuously advanced along the interlayer interface with the help of the rigid support of the main body to obtain the first-level glass fiber sheet. S4, the first-stage glass fiber sheet is heated as a whole, so that the resin matrix inside it softens to a rubber state. The heated first-stage glass fiber sheet is then fed into a roller cutting and layering device for layering and peeling to obtain a second-stage glass fiber sheet.

[0005] As a further improvement of the present invention, the roller cutting and layering device includes upper and lower pressure rollers and a wedge-shaped blade disposed between the two pressure rollers. The upper pressure roller is provided with an elastic pressing adjustment mechanism. The thickness of the second-stage glass fiber sheet is controlled by adjusting the relative height between the wedge-shaped blade disposed between the two pressure rollers and the first-stage glass fiber sheet.

[0006] As a further improvement of the present invention, the temperature of the local heating is higher than the glass transition temperature of the resin matrix in the blank and lower than the thermal decomposition initiation temperature of the resin matrix in the blank, and the heating time is 1 to 5 minutes, wherein the wedging starting end region is a region from the wedging starting end to a depth of 2 to 10 mm.

[0007] As a further improvement of the present invention, the temperature of the overall heating is higher than the glass transition temperature of the resin matrix in the blank and lower than its thermal decomposition initiation temperature, and the holding time after reaching the temperature is 5 to 60 minutes.

[0008] As a further improvement of the present invention, the blank has a thickness of 30-60 mm, a width of 1-10 cm, and a length of 100-500 cm.

[0009] As a further improvement of the present invention, in step S3, the wedge angle of the wedge blade is 5° to 15° and the blade thickness is 1 to 5 mm. The blank is fed in parallel with the wedge blade along the fiber direction, so that the wedge blade continuously wedges in and separates along the fiber interlayer interface to obtain a first-level glass fiber sheet with a thickness of 2 to 20 mm.

[0010] As a further improvement of the present invention, the thickness of the second-level glass fiber sheet is 0.3 to 1.0 mm.

[0011] As a further improvement of the present invention, the method further includes: The second-level fiberglass sheets are surface-treated, and multiple treated second-level fiberglass sheets are woven together to obtain a planar preform. Multiple planar preforms are overlapped to form a stack, and an adhesive is applied to the surface of the stack before hot pressing to obtain a recycled fiberglass board.

[0012] As a further improvement of the present invention, the surface treatment includes: coating the surface of the second-stage glass fiber sheet with a silane coupling agent solution, and then heat curing it at 110-120°C for 10-30 minutes.

[0013] As a further improvement of the present invention, the weaving is to interweave the processed second-level glass fiber sheet along a preset direction to form the planar preform.

[0014] The beneficial effects of this invention are: it achieves high morphological preservation and high-value recycling of continuous glass fibers. This invention employs a graded wedge-in layering strategy, precisely controlling the separation path along the weak interlayer interfaces to progressively dissociate the thick plates of waste wind turbine blades into continuous, elongated strips of controllable thickness. The resulting first-stage glass fiber strips are free of breakage and delamination defects, and their tensile strength, flexural strength, and interlayer shear strength can reach 95-99%, 94-98%, and 92-98% of the original wind turbine blade glass fiberboard, respectively. This fully preserves the original glass fiber length and mechanical strength, significantly enhancing the economic value and reuse potential of the recycled products. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a process flow diagram of a method for recycling waste wind turbine blade fiberglass boards according to an exemplary embodiment of the present invention. Figure 2 This is a physical process diagram of step S3 in a method for recycling waste wind turbine blade fiberglass boards according to an exemplary embodiment of the present invention. Figure 3 This is a comparison diagram of the separated states in a method for recycling waste wind turbine blade fiberglass boards according to an exemplary embodiment of the present invention. Figure 4 This is a physical process diagram of step S4 in a method for recycling waste wind turbine blade fiberglass boards according to an exemplary embodiment of the present invention. Figure 5 This is a physical process diagram of Example 5 of a method for recycling waste wind turbine blade fiberglass boards, which is an exemplary embodiment of the present invention.

[0017] In the picture, 1. Wedge blade; 2. Blank; 3. First-stage fiberglass sheet; 4. Second-stage fiberglass sheet; 5. Planar preform; 6. Lamination; 7. Recycled fiberglass board; 8. Fiberglass skin / balsa wood sandwich panel; 9. Balsa wood. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indicators will also change accordingly.

[0020] Furthermore, the terminology used in the description of this invention is for illustrative purposes only and is not intended to limit the scope of the invention. The terms "comprising" and / or "including" are used to specify the presence of said elements, steps, operations, and / or components, but do not exclude the presence or addition of one or more other elements, steps, operations, and / or components. The terms "first," "second," etc., may be used to describe various elements, do not represent an order, and do not limit these elements. Moreover, in the description of this invention, unless otherwise stated, "a plurality of" means two or more. These terms are used only to distinguish one element from another. These and / or other aspects become apparent in conjunction with the following drawings, and those skilled in the art will more readily understand the description of the embodiments of the invention. The drawings are used for illustrative purposes only to depict the embodiments of the invention. Those skilled in the art will readily recognize from the following description that alternative embodiments of the structures and methods shown in the invention can be employed without departing from the principles of the invention.

[0021] In existing technologies, the industrial disposal methods for waste wind turbine blades mainly include destructive recycling pathways such as mechanical crushing, cement kiln co-processing, high-temperature pyrolysis, and chemical decomposition. Mechanical crushing directly breaks fiberglass boards into a mixture of short fibers and resin powder at the millimeter or even micrometer scale through tearing and grinding, resulting in the near loss of fiber aspect ratio and reinforcing potential; the resulting product can only be used as a low-end filler. Due to the high hardness and brittleness of fiberglass, traditional cutting processes (such as saw blade cutting) generate significant dust and material waste, and it is difficult to cut it into continuous thin sheets like flexible materials such as rubber and sponge. Cement kiln co-processing uses organic resin as an alternative fuel, with the fiberglass component entering the cement clinker, making closed-loop recycling of fiber materials impossible. While high-temperature pyrolysis can recover fibers, high-temperature oxidation and thermal stress often lead to a significant decrease in fiber strength, and energy consumption is high. Chemical decomposition uses supercritical fluids or reactive solvents to depolymerize epoxy resin, facing problems such as harsh reaction conditions, difficulty in solvent recovery, and high wastewater treatment costs.

[0022] In terms of non-destructive utilization, the main beam of discarded wind turbine blades employs a highly oriented fiber layup design to meet unidirectional load-bearing requirements. The tensile strength along the main fiber direction can reach more than twenty times that in the vertical direction, exhibiting significant in-plane anisotropy. This inherent material characteristic determines that the blade main beam plate is essentially a unidirectional load-bearing material, unsuitable for direct use as structural plates requiring bidirectional or multidirectional loads. In practice, discarded wind turbine blade plates are often used as a last resort, directly cut into large strips or columns for crude applications such as fence posts and support piles. However, the original blade plates are typically tens of millimeters thick, resulting in large cross-sectional dimensions and heavy weight in the cut columns, limiting their application to situations where cross-section and weight are not strictly limited. This situation clearly demonstrates that without breaking the original laminated structure to achieve fiber reconfiguration and flexible thickness control, the problem of high-value utilization of discarded blade plates cannot be fundamentally solved.

[0023] From the perspective of laminated structure characteristics, the fiberglass boards of discarded wind turbine blades are mostly multi-layered laminated structures composed of unidirectional fibers. Resin-rich regions exist between the layers, characterized by low fiber penetration, high resin content, and relatively low interfacial bonding strength, forming weak interlayer interfaces. The inventors discovered that by utilizing this weak interlayer interface characteristic, a wedge-shaped cutter can be used at room temperature to initially split the blade material along the interlayer, obtaining fiberglass boards several millimeters to tens of millimeters thick. This demonstrates that macroscopic separation of the interlayers in laminated boards is not impossible. Specifically, after the wedge tip penetrates the interlayer between adjacent fibers, the inclined surface of the wedge generates lateral compressive force on the fracture wall, promoting the directional expansion and transmission of the fracture along the resin-rich region between fibers, thus achieving continuous separation. However, at room temperature, the fiberglass board is hard and brittle, resulting in high resistance and severe wear on the cutter blade during initial wedge insertion. Further experiments revealed that when attempting to cut the aforementioned fiberglass board into even thinner flexible fiberglass sheets, the thicker sheets (several millimeters to tens of millimeters) exhibited high moment of inertia and bending stiffness at room temperature when wedged in, making them less prone to bending deformation and able to withstand wedging forces while remaining straight and achieving stable interlayer separation. However, as the separation thickness gradually decreased to the sub-millimeter level, the bending stiffness of the thin sheets dropped sharply, making them highly susceptible to bending deformation under wedging forces. Furthermore, the epoxy resin matrix, being in a glassy state at room temperature with low fracture toughness, rapidly precipitated brittle fracture after bending deformation, resulting in irregular fragmentation of the sheets before separation was complete, making it impossible to obtain continuous and complete flexible sheets. These experimental results indicate that while room temperature purely mechanical delamination can achieve coarse separation at the millimeter level or higher, it presents technical challenges such as high initial wedging resistance, severe blade wear, and brittle fracture of sub-millimeter-level sheets. Therefore, obtaining flexible sheets directly in one step using purely mechanical methods is technically extremely difficult. In addition, the fiberglass boards for wind turbine blades are thick (usually tens of millimeters), and both the glass fiber and the resin matrix have low thermal conductivity. Heat is transferred slowly in the thickness direction. If the entire board is heated to reach the glass transition temperature of the resin, it will not only consume a lot of energy and take a long time to heat, but also require huge investment in heating equipment and a long process cycle for industrial implementation, which is not economically viable for blades that are tens of meters long.

[0024] To solve the above problems, such as Figure 1 As shown, this invention provides a method for recycling waste wind turbine blade fiberglass boards. The method is applicable to the recycling of waste wind turbine blade main beams, skins, webs, blade roots, and other fiberglass reinforced polymer sheets with laminated structures. The method includes: S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction; Preferably, the blank has a thickness of 30-60 mm, a width of 1-10 cm, and a length of 100-500 cm.

[0025] S2, the starting end of the blank is locally heated, so that only the resin matrix in the area of ​​the starting end of the blank is softened to a rubber state, while the main body of the blank other than the area of ​​the starting end of the blank is kept in an unheated rigid state. Preferably, the local heating temperature is higher than the glass transition temperature of the resin matrix in the preform and lower than the thermal decomposition initiation temperature of the resin matrix in the preform, wherein the local heating temperature is 10-30°C higher than the glass transition temperature of the resin matrix and 30-60°C lower than the thermal decomposition initiation temperature of the resin matrix; preferably, the heating time is 1-5 minutes, wherein the wedging initiation region is a region from the wedging initiation end to a depth of 2-10 mm, and the resin pyrolysis rate is less than 0.2%.

[0026] S3, a wedge-shaped blade is used to wedge into the fiber interlayer interface from the starting area of ​​the wedge, starting from the rubbery resin matrix, and the wedge-shaped blade is continuously advanced along the interlayer interface with the help of the rigid support of the main body to obtain the first-level glass fiber sheet. Preferably, the wedge angle of the wedge-shaped blade is 5° to 15°, and the blade thickness is 1 to 5 mm. Figure 2 As shown, the blank is fed parallel to the wedge-shaped blade along the fiber direction, so that the wedge-shaped blade continuously wedges in and separates along the fiber interlayer interface to obtain a first-level fiberglass sheet with a thickness of 2-20 mm, a width of 1-10 cm, and a length of 100-500 cm. The first-level fiberglass sheet can be used directly as a fiberglass strip to replace commercial products, or after being polished and sprayed with weather-resistant paint, it can be used for agricultural greenhouse frames and other structural applications.

[0027] This invention employs a graded wedge-in and layering strategy, utilizing the reversible thermal softening effect of the glass transition of the resin matrix. Local heating at the wedge initiation point softens the surface resin matrix to a rubbery state, significantly reducing interlayer bonding strength. The remaining bulk of the preform remains in an unheated, rigid state. A wedge-shaped blade wedges in from the initiation point along the fiber interlayer interface, precisely controlling the separation path along the weak interlayer interface. This allows the wedge-shaped blade to initiate cracking smoothly under low resistance conditions, reducing wedge resistance at the initiation point and blade wear. Furthermore, the rigid rear region provides stable support and reaction force for wedge separation, ensuring continuous and stable advancement of the wedge-shaped blade along the interlayer interface. Heating and softening are only used as auxiliary means to lower the initial crack initiation threshold; the main layering process is still completed by the mechanical wedge-shaped blade, thus reducing process difficulty and blade wear while ensuring stable layering efficiency and separation quality.

[0028] This process involves separating waste wind turbine blade fiberglass sheets from raw materials into continuous, long strips of controllable thickness. The resulting first-stage fiberglass sheets are free from breakage and delamination defects, and their tensile strength, bending strength, and interlaminar shear strength can reach 95-99%, 94-98%, and 92-98% of the original wind turbine blade fiberglass sheets, respectively. This fully preserves the original length and mechanical strength of the glass fibers, significantly enhancing the economic value and reuse potential of the recycled products.

[0029] In one alternative implementation, the root section shell of a discarded wind turbine blade, which is the main load-bearing structure at the root of the wind turbine blade, adopts a sandwich structure design. The sandwich structure includes a balsa wood core layer and a thin layer of fiberglass fabric attached to the surface of the balsa wood core layer. When a wedge blade is used to separate the layers, the interface between the first-stage fiberglass layer and the balsa wood core layer can be separated simultaneously.

[0030] S4, the first-stage glass fiber sheet is heated as a whole, so that the resin matrix inside it softens to a rubber state. The heated first-stage glass fiber sheet is then fed into a roller cutting and layering device for layering and peeling to obtain a second-stage glass fiber sheet.

[0031] Specifically, such as Figure 3 As shown, the first-stage glass fiber sheet is uniformly heated to soften the internal resin matrix to a rubbery state, providing low-resistance separation conditions for fine peeling. Preferably, the overall heating temperature is higher than the glass transition temperature of the resin matrix in the preform but lower than its thermal decomposition initiation temperature. The glass transition temperature of the resin matrix is ​​10–30°C, the thermal decomposition initiation temperature is 30–60°C, and the holding time after reaching the temperature is 5–60 minutes, with a resin pyrolysis rate of less than 0.2%. The heated first-stage glass fiber sheet is then rapidly fed into a roller cutting and layering device. The first-stage fiberglass sheet is continuously and precisely peeled off by upper and lower pressure rollers and wedge blades to obtain a thinner and more flexible second-stage fiberglass sheet. The second-stage fiberglass sheet has a thickness of 0.3-1.0 mm, a width of 1-10 cm, and a length of 10-500 cm. Preferably, the roller cutting and layering device includes upper and lower pressure rollers and a wedge blade disposed between the two pressure rollers. The upper pressure roller is provided with an elastic pressing adjustment mechanism. The thickness of the second-stage fiberglass sheet is controlled by adjusting the relative height between the wedge blade disposed between the two pressure rollers and the first-stage fiberglass sheet.

[0032] This invention utilizes the reversible thermal softening effect of the resin's glass transition to solve the problem of brittle fracture during the separation of the first-stage glass fiber sheets. In step S4, the first-stage glass fiber sheet is heated to above the resin's glass transition temperature, causing the resin matrix in the first-stage glass fiber sheet to transform from a glassy state to a rubbery state, significantly improving its fracture toughness. Under the action of wedging force, the softened first-stage glass fiber sheet can undergo coordinated deformation without inducing brittle fracture. Combined with the traction and constraint of the roller cutting and layering device, it becomes possible to continuously and completely peel off the second-stage glass fiber sheets with a thickness of 0.3~1.0 mm. Crucially, the glass transition of epoxy resin is a reversible physical process. After layering and cooling to room temperature, the resin matrix automatically returns to the glassy state and its corresponding mechanical properties. The recovered second-stage glass fiber sheets retain sufficient stiffness and strength, enabling them to perform reliable load-bearing functions in subsequent weaving and hot-pressing reassembly.

[0033] The method described in this invention is green and environmentally friendly, achieving efficient utilization of the resin matrix in conjunction with the process. The core separation step of this invention relies entirely on the synergistic effect of physical-mechanical action and thermal softening, without using corrosive or polluting chemical reagents such as acids, alkalis, or resin depolymerization solvents, and without requiring complete resin pyrolysis as a prerequisite for fiber recycling. The resin matrix is ​​retained during the separation process and can participate in re-curing and cross-linking as an adhesive component in the subsequent hot-pressing molding step, achieving the concurrent recycling and reuse of epoxy resin. The process conditions are mild, energy consumption is low, and it is environmentally friendly. Preferably, the method further includes: S5, the second-level glass fiber sheet is surface treated, and the treated second-level glass fiber sheet is woven to obtain a planar preform. The multiple planar preforms are overlapped to form a stack, and an adhesive is applied to the surface of the stack and then hot-pressed to obtain a recycled glass fiber board.

[0034] Preferably, the surface treatment includes: coating the surface of the second-level glass fiber sheet with a silane coupling agent solution, and then heat curing it at 110-120°C for 10-30 minutes; the weaving is to interweave the treated second-level glass fiber sheet along a preset direction to form the planar preform.

[0035] Specifically, such as Figure 4As shown, a silane coupling agent solution (e.g., 3-glycidyl etheroxypropyltrimethoxysilane) with a mass fraction of 0.5–2.0% is uniformly applied to the surface of the second-stage glass fiber sheet by brushing. It is then heat-cured at 110–120°C for 10–30 minutes to obtain the treated second-stage glass fiber sheet. Multiple treated second-stage glass fiber sheets are interwoven along a preset direction, which can be set according to the actual stress requirements of the recycled board. Preferably, the weaving along the preset direction is orthogonal weaving along the warp and weft directions. The weft sheets are interwoven in a pattern where every 1–3 warp sheets are lifted, forming the planar preform. This structurally eliminates the anisotropy of the raw materials. The planar preform has a thickness of 0.3–2.0 mm, a width of 100–300 cm, and a length of 100–300 cm.

[0036] Multiple planar prefabricated bodies are stacked to form a laminate. An adhesive is applied or impregnated onto the surface of the laminate. The adhesive is one of epoxy, phenolic, unsaturated polyester, or vinyl ester resins. The laminate is then subjected to hot pressing, the conditions of which are determined based on the type of adhesive selected. This process cures the adhesive and bonds the multiple planar prefabricated bodies together. After cooling, a recycled fiberglass board with balanced mechanical properties is obtained. The recycled fiberglass board has a thickness of 2–40 mm, a width of 100–300 cm, and a length of 100–300 cm. The in-plane anisotropy ratio of the recycled fiberglass board is reduced from 25.1:1 in the original fiberglass board to approximately 1:1. The tensile strength, flexural strength, and interlaminar shear strength of the recycled fiberglass board are 50–80%, 50–80%, and 60–85% of the main fiber direction of the waste wind turbine blade fiberglass board, respectively.

[0037] Preferably, when the adhesive is an epoxy resin, the hot-pressing temperature is 120–150°C, the pressure is 0.5–3.0 MPa, and the holding time is 30–90 minutes; when the adhesive is a phenolic resin, the hot-pressing temperature is 150–180°C, the pressure is 0.3–3.0 MPa, and the holding time is 10–60 minutes; when the adhesive is an unsaturated polyester resin, the hot-pressing temperature is 60–120°C, the pressure is 0.5–3.0 MPa, and the holding time is 30–90 minutes; when the adhesive is a vinyl ester resin, the hot-pressing temperature is 60–130°C, the pressure is 0.5–2.0 MPa, and the holding time is 20–60 minutes.

[0038] This invention overcomes the anisotropy limitations of raw materials through orthogonal interlacing, providing flexible and diverse fiber reconstruction paths. Traditional direct cutting and utilization methods cannot change the inherent in-plane anisotropy of waste blade materials, severely limiting their application scenarios. This invention uses the recycled secondary glass fiber sheets as weaving units, reorganizing the fiber orientation through orthogonal interlacing. Furthermore, by adjusting the number of layers, fiber orientation, and weaving parameters, flexible reconstruction paths can be provided for recycled laminates and component blanks of different load-bearing capacities, meeting diverse application needs.

[0039] The following examples illustrate the present application in more detail, but the present application is not limited to these examples as long as it does not depart from its spirit.

[0040] Example 1 S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction. The blanks are 60mm thick, 4cm wide, and 100cm long. S2, the starting end of the blank is locally heated at 160°C for 2 minutes, with a heating depth of 5 mm, so that only the resin matrix in the starting end area is softened to a rubbery state, while the rest of the main body of the blank remains in a rigid state without heating, and the resin pyrolysis rate is 0.02%.

[0041] S3, a wedge-shaped blade is used to cut into the starting end of the wedge along the interlayer direction of the blank. The wedge angle of the wedge is 5° and the blade thickness is 4mm. The blank is fed in parallel with the blade along the fiber direction, so that the wedge blade continuously wedges in and separates along the interlayer interface of the fiber to obtain a first-level fiberglass sheet with a thickness of 5mm, a width of 4cm, and a length of 100cm. The first-level fiberglass sheet has no breakage or delamination defects, and its tensile strength, bending strength, and interlayer shear strength are 98%, 97%, and 95% of those of the waste wind turbine blade fiberglass board, respectively. The obtained first-level fiberglass sheet is heated at 160℃ for 10min to soften the resin in the first-level fiberglass sheet. The resin pyrolysis rate is 0.1%.

[0042] S4, the first-stage fiberglass sheet is heated as a whole, so that the resin matrix inside it softens to a rubber state. The first-stage fiberglass sheet after being heated and softened is quickly fed into the roller cutting and layering device. The first-stage fiberglass sheet is continuously peeled by the upper and lower pressure rollers and the wedge blade to obtain the second-stage fiberglass sheet. The thickness of the second-stage fiberglass sheet is adjusted by adjusting the relative height between the blade and the first-stage fiberglass sheet. The thickness of the second-stage fiberglass sheet is 0.4mm, the width is 4cm and the length is 100cm. S5. The obtained second-level glass fiber sheet is surface-treated with a silane coupling agent. A 1.0% KH560 (3-glycidyl ether oxypropyl trimethoxysilane) solution is applied evenly to the surface of the second-level glass fiber sheet by brushing. Then, it is heat-cured at 110°C for 20 minutes and then woven into a glass fiber mat to form a planar preform. The weaving method is to divide the treated second-level glass fiber sheet into two groups, warp and weft. The weft sheets are interwoven in a pattern where every two warp sheets are picked up. The glass fiber mat has a thickness of 0.8 mm, a width of 100 cm, and a length of 100 cm.

[0043] Four layers of the aforementioned planar prefabricated material are stacked to form a laminate. Epoxy resin is applied to the surface of the laminate, followed by hot pressing. The hot pressing conditions are: pressure 1 MPa, temperature 120℃, and holding time 60 minutes. After cooling to room temperature under holding pressure, the laminate is demolded to prepare a recycled fiberglass board. The recycled fiberglass board has a thickness of approximately 3 mm, a width of 100 cm, and a length of 100 cm. After hot pressing, the in-plane anisotropy ratio of the recycled fiberglass board is reduced from 25.1:1 of the original fiberglass board to approximately 1:1. The tensile strength, flexural strength, and interlaminar shear strength of the recycled fiberglass board are 75%, 78%, and 72% of those of the original wind turbine blade fiberglass board in the main fiber direction, respectively.

[0044] Example 2 S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction. The blanks are 40mm thick, 6cm wide, and 120cm long. S2, the starting end of the blank is locally heated at 170°C for 3 minutes, with a heating depth of 4 mm, so that the surface resin matrix softens to a rubbery state, while the rest of the blank remains in an unheated rigid state, and the resin pyrolysis rate is 0.02%.

[0045] S3, using a wedge-shaped blade to cut into the locally heated starting end of the fiberglass board along the interlayer direction, the wedge angle of the wedge-shaped blade is 6° and the blade thickness is 3.5mm. The blank is fed in parallel with the blade along the fiber direction, so that the wedge-shaped blade continuously wedges in and separates along the fiber interlayer interface, to obtain a first-level fiberglass sheet with a thickness of 3mm, a width of 6cm and a length of 120cm. The first-level fiberglass sheet has no breakage or delamination defects, and its tensile strength, bending strength and interlayer shear strength are 99%, 96% and 96% of those of the waste wind turbine blade fiberglass board, respectively.

[0046] S4, the first-stage fiberglass sheet is heated at 170°C for 8 minutes to soften the resin in the first-stage fiberglass sheet; the resin pyrolysis rate is 0.12%. The softened first-stage fiberglass sheet is quickly fed into a roller cutting and layering device. The first-stage fiberglass sheet is continuously peeled off by upper and lower pressure rollers and wedge blades to obtain a second-stage fiberglass sheet with a thickness of 0.4 mm, a width of 4 cm, and a length of 120 cm.

[0047] S5. The obtained second-stage glass fiber sheet is surface-treated with a silane coupling agent. A 1.0% KH560 (3-glycidyl ether oxypropyl trimethoxysilane) solution is uniformly applied to the surface of the second-stage glass fiber sheet by brushing. Then, it is heat-cured at 110°C for 20 minutes and then woven into a glass fiber mat to form a planar preform. The weaving method is to divide the glass fiber sheet into two groups, warp and weft. The weft sheets are interwoven in a pattern where every 3 warp sheets are picked up. The planar preform has a thickness of 0.8 mm, a width of 120 cm, and a length of 120 cm. Four layers of the planar prefabricated body were stacked, and phenolic resin was applied to the surface of the stack. Then, hot pressing was performed. The hot pressing conditions were 2.5 MPa pressure, 160°C temperature, and 15 minutes holding time. After cooling to room temperature under pressure, the material was demolded to prepare a recycled fiberglass board. The recycled fiberglass board was approximately 3 mm thick, 120 cm wide, and 120 cm long. After hot pressing, the in-plane anisotropy ratio of the recycled fiberglass board decreased from 25.1:1 of the original fiberglass board to nearly 1:1. The tensile strength, flexural strength, and interlaminar shear strength of the recycled fiberglass board were 55%, 58%, and 62% of those of the original wind turbine blade fiberglass board in the main fiber direction, respectively.

[0048] Example 3 S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction. The columnar blanks are 50 mm thick, 2 cm wide, and 200 cm long. S2, the starting end of the blank is locally heated at 150°C for 2 minutes, with a heating depth of 3 mm, so that the surface resin matrix softens to a rubbery state, while the rest of the blank remains unheated, and the resin pyrolysis rate is 0.01%.

[0049] S3, a wedge-shaped blade is used to cut into the starting end of the wedge along the interlayer direction of the fiberglass board. The wedge angle of the wedge is 5° and the blade thickness is 4mm. The columnar blank is fed in parallel with the blade along the fiber direction, so that the wedge-shaped blade continuously wedges in and separates along the interlayer interface of the fiber, to obtain a first-level fiberglass sheet with a thickness of 4mm, a width of 2cm, and a length of 200cm. The first-level fiberglass sheet has no breakage or delamination defects, and its tensile strength, bending strength, and interlayer shear strength are 99%, 98%, and 96% of those of the waste wind turbine blade fiberglass board, respectively. S4. The obtained first-stage fiberglass sheet is heated at 180°C for 8 minutes to soften the resin in the first-stage fiberglass sheet; the resin pyrolysis rate is 0.15%. The softened first-stage fiberglass sheet is quickly fed into a roller cutting and layering device. The first-stage fiberglass sheet is continuously peeled off by upper and lower pressure rollers and wedge blades to obtain a second-stage fiberglass sheet with a thickness of 0.5 mm, a width of 2 cm, and a length of 200 cm.

[0050] S5. The obtained second-stage glass fiber sheet is surface-treated with a silane coupling agent. A 1.0% KH560 (3-glycidyl ether oxypropyl trimethoxysilane) solution is uniformly applied to the surface of the second-stage glass fiber sheet by brushing. Then, it is heat-cured at 110°C for 20 minutes and then woven into a glass fiber mat to form a planar preform. The weaving method is to divide the second-stage glass fiber sheet into two groups, warp and weft. The weft sheets are interwoven in a pattern where every two warp sheets are picked up. The planar preform has a thickness of 1.0 mm, a width of 200 cm, and a length of 200 cm. Five layers of the aforementioned planar prefabricated body were stacked, and epoxy resin was applied to the surface of the stack. The mixture was then subjected to hot pressing, with the conditions being a pressure of 1 MPa, a temperature of 120°C, and a holding time of 60 minutes. After cooling to room temperature under pressure, the material was demolded to prepare a recycled fiberglass board. The recycled fiberglass board was approximately 5 mm thick, 200 cm wide, and 200 cm long. After hot pressing, the in-plane anisotropy ratio of the recycled fiberglass board decreased from 25.1:1 of the original fiberglass board to nearly 1:1. The tensile strength, flexural strength, and interlaminar shear strength of the recycled fiberglass board were 63%, 65%, and 71% of those in the main fiber direction of the waste wind turbine blade fiberglass board, respectively.

[0051] Example 4 S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction. The blanks are 60mm thick, 3cm wide, and 150cm long. S2, the starting end of the wedge is locally heated at 160°C for 2 minutes, with a heating depth of 5 mm, so that the surface resin matrix softens to a rubbery state, while the rest of the blank remains in an unheated rigid state, and the resin pyrolysis rate is 0.02%.

[0052] S3, a wedge-shaped blade is used to cut into the starting end of the wedge along the interlayer direction of the fiberglass board. The wedge angle of the wedge is 6° and the blade thickness is 5mm. The blank is fed in parallel with the blade along the fiber direction, so that the wedge-shaped blade continuously wedges in and separates along the interlayer interface of the fiber to obtain a first-level fiberglass sheet with a thickness of 3mm, a width of 3cm, and a length of 150cm. The first-level fiberglass sheet has no breakage or delamination defects. Its tensile strength, bending strength, and interlayer shear strength are 99%, 98%, and 96% of those of the waste wind turbine blade fiberglass board, respectively. The obtained sheet is polished and painted and sold directly as a commodity flat strip.

[0053] Example 5 like Figure 5 As shown, S1, cut the waste wind turbine blade fiberglass skin / balsa wood sandwich panel into columnar blanks along the fiberglass direction. The blanks are 40 mm thick, 5 cm wide, and 100 cm long. S2, the starting end of the wedge is locally heated at 160°C for 2 minutes, with a heating depth of 5 mm, so that the surface resin matrix softens to a rubbery state, while the rest of the blank remains in an unheated rigid state, and the resin pyrolysis rate is 0.02%.

[0054] S3. Using a wedge-shaped blade, cut into the interface between the glass fiber skin and the balsa wood core layer at a position approximately 1-2 mm off the side of the skin. The wedge angle of the wedge-shaped blade is 6° and the blade thickness is 5 mm. The blank is fed in parallel to the blade along the fiber direction, so that the wedge-shaped blade continuously wedges into and advances to separate the glass fiber skin and balsa wood within the skin layer at this offset position, completely separating the glass fiber skin and balsa wood. The resulting first-stage glass fiber sheet has no balsa wood residue on its surface.

[0055] Numerous specific details are set forth in the specification provided herein. However, it will be understood that embodiments of the invention may be practiced without these specific details. In some instances, well-known methods, structures, and techniques have not been shown in detail so as not to obscure the understanding of this specification.

[0056] Furthermore, those skilled in the art will understand that although some embodiments described herein include certain features but not others included in other embodiments, combinations of features from different embodiments are intended to be within the scope of the invention and form different embodiments. For example, in the claims, any of the claimed embodiments can be used in any combination.

[0057] Those skilled in the art will understand that although the invention has been described with reference to exemplary embodiments, various changes may be made and its elements may be substituted with equivalents without departing from the scope of the invention. Furthermore, many modifications may be made to adapt particular situations or materials to the teachings of the invention without departing from the essential scope of the invention. Therefore, the invention is not limited to the specific embodiments disclosed, but rather the invention will include all embodiments falling within the scope of the appended claims.

Claims

1. A method for recycling fiberglass boards from waste wind turbine blades, characterized in that, The method includes: S1, cut the waste wind turbine blade fiberglass board into columnar blanks along the fiber direction; S2, the starting end of the blank is locally heated, so that only the resin matrix in the area of ​​the starting end of the blank is softened to a rubber state, while the main body of the blank other than the area of ​​the starting end of the blank is kept in an unheated rigid state. S3, a wedge-shaped blade is used to wedge into the fiber interlayer interface from the starting area of ​​the wedge, starting from the rubbery resin matrix, and the wedge-shaped blade is continuously advanced along the interlayer interface with the help of the rigid support of the main body to obtain the first-level glass fiber sheet. S4, the first-stage glass fiber sheet is heated as a whole, so that the resin matrix inside it softens to a rubber state. The heated first-stage glass fiber sheet is then fed into a roller cutting and layering device for layering and peeling to obtain a second-stage glass fiber sheet.

2. The recycling method as described in claim 1, characterized in that, The blank has a thickness of 30-60 mm, a width of 1-10 cm, and a length of 100-500 cm.

3. The recycling method as described in claim 1, characterized in that, The local heating temperature is higher than the glass transition temperature of the resin matrix in the blank and lower than the thermal decomposition initiation temperature of the resin matrix in the blank. The heating time is 1 to 5 minutes. The wedging starting end region is the region from the wedging starting end to a depth of 2 to 10 mm.

4. The recycling method as described in claim 1, characterized in that, In step S3, the wedge angle of the wedge blade is 5° to 15° and the blade thickness is 1 to 5 mm. The blank is fed in parallel with the wedge blade along the fiber direction, so that the wedge blade continuously wedges in and separates along the fiber interlayer interface to obtain a first-level glass fiber sheet with a thickness of 2 to 20 mm.

5. The recycling method as described in claim 1, characterized in that, The overall heating temperature is higher than the glass transition temperature of the resin matrix in the blank and lower than its thermal decomposition initiation temperature. After reaching the temperature, the holding time is 5 to 60 minutes.

6. The recycling method as described in claim 1, characterized in that, The roller cutting and layering device includes upper and lower pressure rollers and a wedge-shaped blade disposed between the two pressure rollers. The upper pressure roller is provided with an elastic pressing adjustment mechanism. The thickness of the second-stage glass fiber sheet is controlled by adjusting the relative height between the wedge-shaped blade disposed between the two pressure rollers and the first-stage glass fiber sheet.

7. The recycling method as described in claim 1, characterized in that, The thickness of the second-level fiberglass sheet is 0.3 to 1.0 mm.

8. The recycling method according to any one of claims 1-7, characterized in that, The method further includes: The second-level fiberglass sheets are surface-treated, and multiple treated second-level fiberglass sheets are woven together to obtain a planar preform. Multiple planar preforms are overlapped to form a stack, and an adhesive is applied to the surface of the stack before hot pressing to obtain a recycled fiberglass board.

9. The recycling method as described in claim 8, characterized in that, The surface treatment includes: coating the surface of the second-stage glass fiber sheet with a silane coupling agent solution, followed by heat curing at 110-120°C for 10-30 minutes.

10. The recycling method as described in claim 8, characterized in that, The weaving involves interlacing the treated second-level glass fiber sheets along a predetermined direction to form the planar preform.